PENGEMBANGAN MEDIA MISTERY BOX PADA MATA PELAJARAN IPAS MATERI SISTEM PENCERNAAN UNTUK MENDUKUNG MINAT BELAJAR SISWA KELAS V SEKOLAH DASAR - Kodiriyah, Ain Nun Sila; Sutrisno AB, Joko; Rahmawati, Endah (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2025)
This development research is motivated by the problem of less varied learning and low interest in learning among students. Teachers only use textbooks due to the lack of availability of learning media. This study aims to develop mystery box media, determine the feasibility of the media and the effectiveness of the media to support student interest. This research and development uses the ADDIE model with five stages, namely analysis, design, development, implementation and evaluation. Data collection techniques in this study are observation, interviews, and questionnaires. Based on the results of the validation of experts, the values obtained were material experts of 86.15% with the criteria of